Inclusive learning model with local wisdom for gender equality in physical education - Yoda, I Ketut; Artanayasa, I Wayan; Wijaya, Made Agus; Hita, I Putu Agus Dharma; Andika, I Putu Herry Widhi (LPMPP Universitas Negeri Yogyakarta, 2025)
This study aims to develop an Inclusive Learning Model Based on Local Wisdom, oriented towards gender equality and disability in Physical Education (PJOK), to build Fundamental Motor Skills and character in students. The research utilizes the ADDIE method, which consists of five stages: analysis, design, development, implementation, and evaluation. In the analysis phase, the causes of gaps in PJOK learning were identified through interviews and observations. The design phase produced a draft method that accommodates individual needs, focusing on gender equality and disabilities. In the development phase, validation by experts indicated that the method is based on solid theory and is practically applicable in the classroom. During the implementation phase, the product was tested on small and large groups, showing high practicality and effectiveness. Comparative testing across three schools in Buleleng further reinforced the effectiveness of the model in enhancing students' locomotor and manipulative motor skills. Statistical analysis (descriptive, normality, homogeneity, and independent sample tests) showed significant improvements in student achievement. The findings conclude that the Inclusive Learning Model based on local wisdom is effective, valid, and practical in improving students' learning outcomes in PJOK.